Multiband electrochromic composite film as well as preparation method and application thereof

By preparing WO3-x precursor colloid under ice water bath conditions and adding titanium source to form composite colloids, combined with spin coating and annealing processes, the problems of complex process of preparing multi-band electrochromic composite films in the prior art and insufficient modulation performance are solved, and dynamic modulation of visible-near-infrared light and efficient modulation of mid-infrared bands are achieved.

CN119805829APending Publication Date: 2025-04-11江淮前沿技术协同创新中心 +1

Patent Information

Application Number
CN202510185420.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, when preparing multi-band electrochromic composite films, the process is complicated, it is difficult to ensure the uniformity and reproducibility of the film, and the modulation performance in the mid-infrared band is insufficient.

Method used

WO3-x precursor colloid was prepared under ice water bath conditions, and titanium source was added for ultrasonic hydrolysis to form WO3-x/TiO2 composite precursor colloid, which was then spin-coated on a transparent conductive substrate. After carbonization and annealing treatment, a multi-band electrochromic composite film was prepared.

Benefits of technology

Dynamic modulation of visible-near-infrared light is achieved, with three optical modes: "bright and hot", "bright and cold" and "dark and cold", and has a high emissivity modulation capability in the mid-infrared band, which improves the stability and optical performance of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119805829A_ABST
    Figure CN119805829A_ABST
Patent Text Reader

Abstract

The invention relates to a multiband electrochromic composite film and a preparation method and application thereof, and belongs to the technical field of optical devices and preparation thereof. In order to solve the technical problem that in the prior art, the optical performance and the like of an electrochromic film in visible / near-infrared / mid-infrared areas need to be improved, the multiband electrochromic composite film has the optical modulation amplitude of 70%-78% under the light wavelength of 700 nm; and / or, the optical modulation amplitude is 65%-72% under the condition that the optical wavelength is 1200 nm; and / or in the bright hot mode, the light transmittance is 75%-82% under the light wavelength of 550 nm, and the light transmittance is 70%-75% under the light wavelength of 1200 nm; and / or in the bright cold mode, the light transmittance is 65%-72% under the light wavelength of 550 nm, and the light transmittance is 28%-35% under the light wavelength of 1200 nm; and / or in the dark cold mode, the light transmittance is 23%-28% under the light wavelength of 550 nm, and the light transmittance is 0.8%-2% under the light wavelength of 1200 nm. The method can be applied to intelligent window and spacecraft thermal management. The invention further provides a preparation method of the multiband electrochromic composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of optical devices and preparation thereof, and in particular, relates to a multi-band electrochromic composite film and a preparation method and application thereof. Background Art

[0002] Windows are the main way of heat exchange between indoor and outdoor, and the energy lost through windows accounts for a large part of the total energy consumption of buildings. This means that the development of a new generation of glass can reduce the building energy consumption of traditional glass. In recent decades, various technologies dedicated to improving the energy efficiency of window systems have made significant progress, such as electrochromic, thermochromic, photochromic and gasochromic smart windows. Among them, electrochromic smart windows can dynamically adjust the transmittance of sunlight by a very small voltage, which has the advantage of active control. Electrochromic materials are an important component of electrochromic smart windows. Compared with organic materials, inorganic electrochromic materials such as WO3, TiO2, NiO, V2O5 and other transition metal oxides are more stable. In particular, WO3 is well known for its high optical modulation amplitude and high coloring efficiency, but most of the current research is limited to the regulation of WO3 on visible light, and there is a lack of systematic research on the regulation of near-infrared and mid-infrared regions. The main reason is that the ITO or FTO materials used as electrochromic transparent conductive layers have low infrared transmittance. Therefore, some alternative transparent electrode materials, including AgNW and MXene, have been widely studied. However, these emerging transparent electrode materials still face many technical challenges, such as high cost and complex manufacturing process, and low modulation amplitude in the near-infrared and mid-infrared.

[0003] At present, people mainly optimize the light modulation performance of materials from the microstructure and composite doping of materials. As we all know, TiO2 has high transparency, corrosion resistance, high temperature stability, high infrared transmittance, and is often used to design anti-reflection coatings. Studies have shown that the electrochromic properties of WO3 can be improved by doping or compounding TiO2 into WO3. In addition, since invisible infrared light accounts for half of all solar radiation on the earth's surface, it is particularly important to develop new multi-band responsive WO3 electrochromic films based on low-cost ITO.

[0004] For example, the Chinese patent application publication number is CN113800781A, the application date is September 14, 2021, and the name is a tungsten trioxide-titanium dioxide electrochromic film and its preparation method. The disclosed preparation method uses conductive glass as a substrate and adopts a hydrothermal method to prepare a layer of TiO2 array film; then a secondary hydrothermal reaction is performed to grow WO3 on the TiO2 array to obtain an electrochromic film. This scheme has the following problems: (1) Although the process of preparing TiO2 array film by hydrothermal method and growing WO3 by secondary hydrothermal reaction is relatively simple, it still requires precise control of reaction conditions such as temperature, time and solution concentration, which increases the complexity of the process and the requirements for equipment. (2) The hydrothermal method may be difficult to ensure the uniformity and reproducibility of the film in large-scale production. The film performance between different batches may vary, which requires strict quality control and process optimization. (3) Although the film obtained by this scheme has dual-frequency regulation function in the visible-near infrared band, it lacks regulation of its own thermal radiation in the mid-infrared band, and the optical modulation amplitude in some bands is still not ideal. In addition, the films prepared by the hydrothermal method may be deficient in mechanical strength and adhesion.

[0005] Therefore, it is an urgent problem to prepare multi-band electrochromic composite films through a simple and economical method for optical modulation in the visible-near-infrared-mid-infrared region. Summary of the invention

[0006] 1. Problems to be solved

[0007] In view of the technical problems that the optical performance of electrochromic films in the visible / near infrared / mid-infrared regions in the prior art needs to be improved, this application provides a multi-band electrochromic composite film and its application;

[0008] Furthermore, the present invention also provides a method for preparing the multi-band electrochromic composite film.

[0009] 2. Technical solution

[0010] In order to achieve the above purpose, the technical solution provided is:

[0011] Based on the purpose of the present invention, the first aspect of the present invention provides a multi-band electrochromic composite film, the film having:

[0012] An optical modulation amplitude of 70% to 78% at a light wavelength of 700 nm; and / or,

[0013] An optical modulation amplitude of 65% to 72% at a light wavelength of 1200 nm; and / or,

[0014] In the "bright heat" mode, the transmittance is 75% to 82% at a wavelength of 550nm and the transmittance is 70% to 75% at a wavelength of 1200nm; and / or,

[0015] In the "bright cold" mode, the transmittance is 65% to 72% at a wavelength of 550nm, and the transmittance is 28% to 35% at a wavelength of 1200nm; and / or,

[0016] In the "dark and cold" mode, the transmittance is 23% to 28% at a light wavelength of 550nm, and the transmittance is 0.8% to 2% at a light wavelength of 1200nm.

[0017] According to any embodiment of the first aspect of the present invention, the multi-band electrochromic composite film further comprises:

[0018] In the 8.5 μm to 9.5 μm band, an emissivity modulation amplitude of 0.4 to 0.6; and / or,

[0019] In the 9.5μm to 13μm band, the emissivity modulation amplitude is 0.2 to 0.4.

[0020] According to any embodiment of the first aspect of the present invention, the multi-band electrochromic composite film has a thickness of 0.2 μm to 1.5 μm.

[0021] According to the multi-band electrochromic composite film of any embodiment of the first aspect of the present invention, in the X-ray photoelectron energy spectrum, the 4f electron orbit of tungsten element has characteristic peaks at binding energies of 35.8 eV, 37.9 eV, 34.6 eV, and 36.6 eV.

[0022] According to the multi-band electrochromic composite film of any embodiment of the first aspect of the present invention, in the X-ray photoelectron spectrum, the 2p electron orbit of the titanium element has a characteristic peak at a binding energy of 458.9 eV or 464.7 eV.

[0023] Based on the purpose of the present invention, the second aspect of the present invention provides a method for preparing a multi-band electrochromic composite film, comprising the following steps:

[0024] S1. Add 5-10 mL H2O2 to every 1-3 g tungsten powder in an ice-water bath, stir slowly until the solution is transparent, add AcOH and EtOH in sequence, continue stirring until the solution is clear, and after aging, obtain WO 3-x Precursor colloid; the volume ratio of H2O2, AcOH, and EtOH is 5-10:1-3:5-10;

[0025] S2. The WO 3-x Titanium source was added to the precursor colloid and ultrasonic hydrolyzed to obtain WO 3-x / TiO2 composite precursor colloid, use 126-378μL titanium source for every 1-3g tungsten powder;

[0026] S3. The WO 3-x After adding a film-forming agent to the TiO2 composite precursor colloid, the film is spin-coated on a transparent conductive substrate, carbonized at 150°C to 250°C for 10min to 30min, gradually heated to 350°C to 450°C, and annealed to obtain the film.

[0027] According to the method for preparing a multi-band electrochromic composite film in any embodiment of the second aspect of the present invention, the transparent conductive substrate is ITO glass or FTO glass.

[0028] According to the method for preparing a multi-band electrochromic composite film in any embodiment of the second aspect of the present invention, the titanium source is one or more of tetramethyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate or tetraethyl titanate.

[0029] According to the method for preparing a multi-band electrochromic composite film of any embodiment of the second aspect of the present invention, the film-forming agent is PEG600; and the added amount of the film-forming agent is 0.07 mL to 0.28 mL.

[0030] Based on the purpose of the present invention, the third aspect of the present invention provides an application of a multi-band electrochromic composite film, and the application of the film in the preparation of smart windows, smart car windows, electrochromic displays, smart thermal management materials or color-changeable camouflage military equipment.

[0031] Any embodiment of any aspect of the present invention can be combined with other embodiments without contradiction. In addition, in any embodiment of any aspect of the present invention, any technical feature can be applied to the technical feature in other embodiments without contradiction.

[0032] Under the premise that there is no contradiction, any technical feature of any aspect of the present invention or any embodiment of any aspect is also applicable to any other embodiment or any embodiment of any other aspect. Of course, when applicable to each other, the corresponding features can be appropriately modified if necessary. The various aspects and features of the present invention are further described below.

[0033] 3. Beneficial effects

[0034] Compared with the existing known technology, the technical solution provided by the present invention has the following beneficial effects:

[0035] (1) The multi-band electrochromic composite film of the present invention can achieve dynamic modulation of visible-near infrared light at different voltages, and has three optical modes: "bright and hot", "bright and cold", and "dark and cold". Bright and hot mode: Under a positive bias voltage, the film has a high transmittance in the visible-near infrared region. Bright and cold mode: Under a small negative bias voltage, the transmittance of the film in the visible light region remains almost unchanged, while the near infrared transmittance is greatly reduced. Dark and cold mode: Under a large negative bias voltage, the visible-near infrared transmittance of the film is greatly reduced. It shows a high optical modulation amplitude in the visible light and near infrared regions.

[0036] Mid-infrared emissivity regulation: The emissivity modulation of the film in the mid-infrared region (8.5μm - 9.5μm and 9.5μm - 13μm) is about 0.5 and 0.3 respectively. In the bleached state, the film exhibits a low emissivity and a low temperature, showing the "bright and hot" mode. At the same time, the low emissivity ensures low thermal radiation emitted outward, further enhancing the "bright and hot" mode. In the colored state, the film exhibits a high emissivity and a high temperature, showing the "dark and cold" mode, realizing the coordinated regulation of three bands.

[0037] Microstructure optimization: By adding Ti element, WO3 is transformed from monoclinic phase to cubic phase, improving the stability of the film. The film surface is relatively flat, showing a porous structure, and the average thickness is about 1.4μm, which is beneficial to the diffusion of ions and the improvement of electrochromic performance.

[0038] Introduction of oxygen vacancies: Oxygen vacancies are introduced by the carbothermal reduction method, confirming the existence of WO 3-x (0 < x < 0.5). The existence of oxygen vacancies is beneficial to the improvement of electrochromic performance.

[0039] (2) The preparation method of the multi-band electrochromic composite film of the present invention is to prepare a precursor colloid and a WO 3-x / TiO2 composite precursor colloid, and then prepare the multi-band electrochromic composite film through spin coating and annealing processes. The operation is simple, the cost is low, the energy consumption is low, and it is suitable for large-scale production.

[0040] (3) The application of the multi-band electrochromic composite film of the present invention is highly efficient and energy-saving: Compared with ordinary glass windows, multi-band electrochromic smart windows can significantly save building energy consumption. Dynamic spectral regulation: By adjusting the transmittance of visible light and near-infrared light, three optical modes of "bright heat", "bright cold" and "dark cold" are realized, effectively controlling indoor temperature and lighting, and improving living comfort. Automobile industry: When used in car windows, the transmittance can be automatically adjusted according to the external environment, reducing the driver's visual fatigue and improving driving safety. At the same time, by adjusting the transmittance of near-infrared light, the temperature change in the car is reduced and the comfort is improved. Military camouflage: used in military equipment and clothing, the dynamic change of camouflage patterns is realized through electrochromic technology, the camouflage effect is improved, and the probability of being discovered by the enemy is reduced. Thermal management: Intelligent thermal management materials: Thermal management of the surface of an object is achieved by adjusting the infrared emissivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 For WO 3-x Preparation flow chart and application of / TiO2 composite films.

[0042] Figure 2 The microstructure and morphology of Example 3 are characterized. Among them: (a) XRD spectrum of multi-band electrochromic composite film W4 on ITO. (b) Full XPS spectrum of multi-band electrochromic composite film W4. (c) W 4f high-resolution XPS spectrum of multi-band electrochromic composite film W4. (d) Ti 2p high-resolution XPS spectrum of multi-band electrochromic composite film W4. (e) SEM image of multi-band electrochromic composite film W4. (f) Cross-sectional SEM image of multi-band electrochromic composite film W4.

[0043] Figure 3 The optical performance diagram of the film W4 prepared in Example 3. Among them: (a) Visible-near infrared optical modulation of W4. (b) Optical modulation of W4 at different voltages. (c) Optical modulation change of W4 after 1000 CV cycles. (d) Three optical mode function diagrams of W4.

[0044] Figure 4 Mid-infrared thermal image and emissivity diagram of the film W4 obtained in Example 3. Wherein: (a) Schematic diagram of W4 placed on a heating table in the colored and faded states. (b) Infrared thermal image of W4 in the colored and faded states. (c) Emissivity modulation diagram of the mid-infrared 8μm to 13μm. DETAILED DESCRIPTION

[0045] In order to further understand the content of the present invention, the present invention is described in detail in conjunction with embodiments.

[0046] The preparation method of the multi-band electrochromic composite film in the embodiment of the present application is as follows: Figure 1 As shown, the specific preparation steps are as follows:

[0047] S1. Preparation of WO 3-x Precursor colloid

[0048] Add 1-3g tungsten powder to a beaker, then slowly add 5mL-10mL H2O2 while stirring slowly. The whole process is carried out in an ice-water bath. Continue stirring until the solution is almost transparent. Add 1mL-3mL AcOH (≥99.5wt%) and 5mL-10mL EtOH (≥99.7wt%) in sequence. Continue stirring until the solution becomes clear. After aging for several hours, a yellow-green transparent sol is obtained, which is WO 3-x Precursor colloid.

[0049] S2. Preparation of WO 3-x / TiO2 composite precursor colloid

[0050] The WO obtained in step S1 3-x 126 μL to 378 μL of titanium source, such as tetramethyl titanate, tetraisopropyl titanate, tetrabutyl titanate or tetraethyl titanate, is added to the precursor colloid, and ultrasonically hydrolyzed for a period of time to form a uniform orange-red transparent sol, namely WO 3-x / TiO2 composite precursor colloid.

[0051] S3. Preparation of multi-band electrochromic composite films

[0052] The WO obtained in step S2 3-x A film-forming agent, such as 0.07mL to 0.28mL of PEG600, is added to the TiO2 composite precursor colloid. A 25mm*25mm transparent conductive substrate, such as ITO glass or FTO glass, is ultrasonically cleaned with acetone, ethanol, and deionized water for 15 minutes, and then one side is sealed with a 5mm wide tape. The above colloid is spin-coated on a transparent conductive substrate with a rotation speed of 1500rpm to 8000rpm and a spin coating time of 20s using a spin coater, and then the tape is removed and placed on a heating platform at 150℃ to 250℃ for 10min to 30min to carbonize the organic matter therein, and more oxygen vacancies are formed by carbon thermal reduction. Finally, it is placed in a muffle furnace and heated to 350℃ to 450℃ at a heating rate of 5℃ / min, and annealed for 0.5h to 1.5h to obtain a multi-band electrochromic composite film.

[0053] The specific process parameters and results of each embodiment of the present application are as follows.

[0054] Example 1

[0055] This embodiment includes the following steps:

[0056] Step S1. Add 1g of tungsten powder to a beaker, then slowly add 5mL of H2O2 while slowly stirring. The whole process is carried out in an ice-water bath. Continue stirring until the solution is nearly transparent. Then add 1mL of AcOH (≥99.5wt%) and 5mL of EtOH (≥99.7wt%) in sequence. Continue stirring until the solution becomes clear. After aging for several hours, a yellow-green transparent sol is obtained, which is WO 3-x Precursor colloid.

[0057] Step S2. WO obtained in step S1 3-x 126 μL of tetrabutyl titanate was added to the precursor colloid and ultrasonically hydrolyzed for a period of time to form a uniform orange-red transparent sol, namely WO 3-x / TiO2 composite precursor colloid.

[0058] Step S3. WO obtained in step S2 3-x 0.07mL PEG600 was added to the TiO2 composite precursor colloid as a film-forming agent, and the 25mm*25mm ITO glass was ultrasonically cleaned with acetone, ethanol, and deionized water for 15 minutes, and then one side was sealed with a 5mm wide tape. The above colloid was spin-coated on the ITO glass with a spin coater at a speed of 8000rpm and a spin coating time of 20s, and then the tape was torn off and placed on a heating platform at 150℃ for 10 minutes to carbonize the organic matter therein, and more oxygen vacancies were formed by carbon thermal reduction. Finally, it was placed in a muffle furnace and heated to 350℃ at a heating rate of 5℃ / min, and annealed for 0.5h to obtain a multi-band electrochromic composite film.

[0059] The film prepared in this example has a thickness of 0.2 μm.

[0060] There is a large optical modulation amplitude in the visible and near-infrared regions (71% at 700nm and 67% at 1200nm), which can realize switching between the three modes of "bright and hot", "bright and cold", and "dark and cold".

[0061] In “bright heat” mode, high transmission of visible and near-infrared light is allowed (82% at 550nm and 75% at 1200nm).

[0062] In the "bright-cool" mode, the transmittance of visible light remains almost unchanged, and the transmittance of near-infrared light is greatly reduced (72% at 550nm and 35% at 1200nm).

[0063] In the "dark cool" mode, the visible and near-infrared light transmittance drops further (28% at 550nm and 2% at 1200nm).

[0064] The self-thermal radiation in the mid-infrared also changes before and after the color change. At 8.5μm~9.5μm, the emissivity modulation is 0.43, and at 9.5μm~13μm, the emissivity modulation is 0.25.

[0065] Example 2

[0066] S1. Add 3g tungsten powder to a beaker, then slowly add 10mL H2O2 while stirring slowly. The whole process is carried out in an ice water bath. Continue stirring until the solution is almost transparent. Then add 3mL AcOH (≥99.5wt%) and 10mL EtOH (≥99.7wt%) in sequence. Continue stirring until the solution becomes clear. After aging for several hours, a yellow-green transparent sol is obtained, which is WO 3-x Precursor colloid.

[0067] S2. WO obtained in step S1 3-x 378 μL of tetrabutyl titanate was added to the precursor colloid and ultrasonically hydrolyzed for a period of time to form a uniform orange-red transparent sol, namely WO 3-x / TiO2 composite precursor colloid.

[0068] S3. WO obtained in step S2 3-x 0.28mL PEG600 was added to the TiO2 composite precursor colloid as a film-forming agent. The 25mm*25mm ITO glass was ultrasonically cleaned with acetone, ethanol and deionized water for 15 minutes respectively, and then one side was sealed with a 5mm wide tape. The above colloid was spin-coated on the ITO glass with a spin coater at a speed of 1500rpm and a spin coating time of 20s, and then the tape was torn off and placed on a heating platform at 250℃ for 30 minutes to carbonize the organic matter therein, and more oxygen vacancies were formed by carbon thermal reduction. Finally, it was placed in a muffle furnace and heated to 450℃ at a heating rate of 5℃ / min, and annealed for 1.5h to obtain a multi-band electrochromic composite film.

[0069] The film prepared in this example has a thickness of 1.5 μm.

[0070] There is a large optical modulation amplitude in the visible and near-infrared regions (70% at 700nm and 65% at 1200nm), which can realize switching between the three modes of "bright and hot", "bright and cold", and "dark and cold".

[0071] In "bright heat" mode, high transmission of visible and near-infrared light is allowed (75% at 550nm and 70% at 1200nm).

[0072] In the "bright-cool" mode, the transmittance of visible light remains almost unchanged, and the transmittance of near-infrared light is greatly reduced (65% at 550nm and 28% at 1200nm).

[0073] In the "dark cool" mode, the visible and near-infrared light transmittance drops further (23% at 550nm and 0.8% at 1200nm).

[0074] The self-thermal radiation in the mid-infrared also changes before and after the color change. At 8.5μm~9.5μm, the emissivity is modulated by 0.6, and at 9.5μm~13μm, the emissivity is modulated by 0.4.

[0075] Example 3

[0076] S1. Add 3g tungsten powder to a beaker, then slowly add 10mL H2O2 while stirring slowly. The whole process is carried out in an ice water bath. Continue stirring until the solution is almost transparent. Then add 3mL AcOH (≥99.5wt%) and 10mL EtOH (≥99.7wt%) in sequence. Continue stirring until the solution becomes clear. After aging for several hours, a yellow-green transparent sol is obtained, which is WO 3-x Precursor colloid.

[0077] S2. WO obtained in step S1 3-x 252 μL of tetrabutyl titanate was added to the precursor colloid and ultrasonically hydrolyzed for a period of time to form a uniform orange-red transparent sol, namely WO 3-x / TiO2 composite precursor colloid.

[0078] S3. WO obtained in step S2 3-x 0.14mL PEG600 was added to the colloid of the TiO2 composite precursor as a film-forming agent. The 25mm*25mm ITO glass was ultrasonically cleaned with acetone, ethanol, and deionized water for 15 minutes, and then one side was sealed with a 5mm wide tape. The above colloid was spin-coated on the ITO glass with a spin coater at a speed of 2000rpm and a spin coating time of 20s, and then the tape was torn off and placed on a heating platform at 250℃ for 30 minutes to carbonize the organic matter therein, and more oxygen vacancies were formed by carbon thermal reduction. Finally, it was placed in a muffle furnace and heated to 400℃ at a heating rate of 5℃ / min, and annealed for 1h to obtain a multi-band electrochromic composite film, named W4.

[0079] The film prepared in this example has a thickness of 1.4 μm.

[0080] There is a large optical modulation amplitude in the visible and near-infrared regions (76.22% at 700nm and 70.87% at 1200nm), which can realize switching between the three modes of "bright and hot", "bright and cold", and "dark and cold".

[0081] In the “bright heat” mode, high transmission of visible and near-infrared light is allowed (79.01% at 550nm and 72.29% at 1200nm).

[0082] In the “bright-cold” mode, the transmittance of visible light remains almost unchanged, and the transmittance of near-infrared light is greatly reduced (70.28% at 550nm and 30.38% at 1200nm).

[0083] In the “dark and cool” mode, the visible and near-infrared light transmittances further decrease (26.72% at 550nm and 1.42% at 1200nm).

[0084] The self-thermal radiation in the mid-infrared also changes before and after the color change. At 8.5μm~9.5μm, the emissivity is modulated by 0.5, and at 9.5μm~13μm, the emissivity is modulated by 0.3.

[0085] Example 4

[0086] S1. Add 3g tungsten powder to a beaker, then slowly add 10mL H2O2 while stirring slowly. The whole process is carried out in an ice water bath. Continue stirring until the solution is almost transparent. Then add 3mL AcOH (≥99.5wt%) and 10mL EtOH (≥99.7wt%) in sequence. Continue stirring until the solution becomes clear. After aging for several hours, a yellow-green transparent sol is obtained, which is WO 3-x Precursor colloid.

[0087] S2. WO obtained in step S1 3-x 126 μL of tetrabutyl titanate was added to the precursor colloid and ultrasonically hydrolyzed for a period of time to form a uniform orange-red transparent sol, namely WO 3-x / TiO2 composite precursor colloid.

[0088] S3. WO obtained in step S2 3-x 0.14mL PEG600 was added to the TiO2 composite precursor colloid as a film-forming agent. The 25mm*25mm ITO glass was ultrasonically cleaned with acetone, ethanol and deionized water for 15 minutes respectively, and then one side was sealed with a 5mm wide tape. The above colloid was spin-coated on the ITO glass with a spin coater at a speed of 2000rpm and a spin coating time of 20s, and then the tape was torn off and placed on a heating platform at 250℃ for 30 minutes to carbonize the organic matter therein, and more oxygen vacancies were formed by carbon thermal reduction. Finally, it was placed in a muffle furnace and heated to 400℃ at a heating rate of 5℃ / min, and annealed for 1h to obtain a multi-band electrochromic composite film.

[0089] The film prepared in this example has a thickness of 0.8 μm.

[0090] There is a large optical modulation amplitude in the visible and near-infrared regions (73% at 700nm and 69% at 1200nm), which can realize switching between the three modes of "bright and hot", "bright and cold", and "dark and cold".

[0091] In “bright heat” mode, high transmission of visible and near-infrared light is allowed (78% at 550nm and 73% at 1200nm).

[0092] In the "bright-cool" mode, the transmittance of visible light remains almost unchanged, and the transmittance of near-infrared light is greatly reduced (68% at 550nm and 32% at 1200nm).

[0093] In the "dark cool" mode, the visible and near-infrared light transmittance drops further (27% at 550nm and 1.1% at 1200nm).

[0094] The self-thermal radiation in the mid-infrared also changes before and after the color change. At 8.5μm~9.5μm, the emissivity modulation is 0.49, and at 9.5μm~13μm, the emissivity modulation is 0.28.

[0095] Example 5

[0096] S1. Add 3g tungsten powder to a beaker, then slowly add 10mL H2O2 while stirring slowly. The whole process is carried out in an ice water bath. Continue stirring until the solution is almost transparent. Then add 3mL AcOH (≥99.5wt%) and 10mL EtOH (≥99.7wt%) in sequence. Continue stirring until the solution becomes clear. After aging for several hours, a yellow-green transparent sol is obtained, which is WO 3-x Precursor colloid.

[0097] S2. WO obtained in step S1 3-x 378 μL of tetrabutyl titanate was added to the precursor colloid and ultrasonically hydrolyzed for a period of time to form a uniform orange-red transparent sol, namely WO 3-x / TiO2 composite precursor colloid.

[0098] S3. WO obtained in step S2 3-x 0.14mL PEG600 was added to the TiO2 composite precursor colloid as a film-forming agent. The 25mm*25mm ITO glass was ultrasonically cleaned with acetone, ethanol and deionized water for 15 minutes respectively, and then one side was sealed with a 5mm wide tape. The above colloid was spin-coated on the ITO glass with a spin coater at a speed of 2000rpm and a spin coating time of 20s, and then the tape was torn off and placed on a heating platform at 250℃ for 30 minutes to carbonize the organic matter therein, and more oxygen vacancies were formed by carbon thermal reduction. Finally, it was placed in a muffle furnace and heated to 400℃ at a heating rate of 5℃ / min, and annealed for 1h to obtain a multi-band electrochromic composite film.

[0099] The film prepared in this example has a thickness of 1.4 μm.

[0100] There is a large optical modulation amplitude in the visible and near-infrared regions (77% at 700nm and 66% at 1200nm), which can realize switching between the three modes of "bright and hot", "bright and cold", and "dark and cold".

[0101] In “bright heat” mode, high transmission of visible and near-infrared light is allowed (76% at 550nm and 71% at 1200nm).

[0102] In the "bright-cool" mode, the transmittance of visible light remains almost unchanged, and the transmittance of near-infrared light is greatly reduced (69% at 550nm and 29% at 1200nm).

[0103] In the "dark cool" mode, the visible and near-infrared light transmittance drops further (24% at 550nm and 0.9% at 1200nm).

[0104] The self-thermal radiation in the mid-infrared also changes before and after the color change. At 8.5μm~9.5μm, the emissivity is modulated by about 0.6, and at 9.5μm~13μm, the emissivity is modulated by about 0.31.

[0105] Example 6

[0106] The preparation method of this embodiment is basically the same as that of Embodiment 3, except that the glass used in this embodiment is FTO glass.

[0107] The film prepared in this example has a thickness of 1.4 μm.

[0108] There is a large optical modulation amplitude in the visible and near-infrared regions (78% at 700nm and 72% at 1200nm), which can realize switching between the three modes of "bright and hot", "bright and cold", and "dark and cold".

[0109] In “bright heat” mode, high transmission of visible and near-infrared light is allowed (81% at 550nm and 75% at 1200nm).

[0110] In the "bright-cool" mode, the transmittance of visible light remains almost unchanged, and the transmittance of near-infrared light is greatly reduced (72% at 550nm and 33% at 1200nm).

[0111] In the "dark cool" mode, the visible and near-infrared light transmittance drops further (26% at 550nm and 0.9% at 1200nm).

[0112] The self-thermal radiation in the mid-infrared also changes before and after the color change. At 8.5μm~9.5μm, the emissivity is modulated by 0.5, and at 9.5μm~13μm, the emissivity is modulated by 0.4.

[0113] Example 7

[0114] The preparation method of this embodiment is basically the same as that of Embodiment 3, except that the titanium source used in this embodiment is tetraethyl titanate.

[0115] The film prepared in this example has a thickness of 1.4 μm.

[0116] There is a large optical modulation amplitude in the visible and near-infrared regions (76% at 700nm and 72% at 1200nm), which can realize switching between the three modes of "bright and hot", "bright and cold", and "dark and cold".

[0117] In “bright heat” mode, high transmission of visible and near-infrared light is allowed (82% at 550nm and 73% at 1200nm).

[0118] In the "bright-cool" mode, the transmittance of visible light remains almost unchanged, and the transmittance of near-infrared light is greatly reduced (70% at 550nm and 34% at 1200nm).

[0119] In the "dark cool" mode, the visible and near-infrared light transmittance drops further (25% at 550nm and 1.7% at 1200nm).

[0120] The self-thermal radiation in the mid-infrared also changes before and after the color change. At 8.5μm~9.5μm, the emissivity modulation is 0.49, and at 9.5μm~13μm, the emissivity modulation is 0.26.

[0121] Example 8

[0122] The preparation method of this embodiment is basically the same as that of embodiment 3, except that the spin coating speed of this embodiment is 7000 rpm.

[0123] The film prepared in this example has a thickness of 0.24 μm.

[0124] There is a large optical modulation amplitude in the visible and near-infrared regions (76.5% at 700nm and 71% at 1200nm), which can realize switching between the three modes of "bright and hot", "bright and cold", and "dark and cold".

[0125] In “bright heat” mode, high transmission of visible and near-infrared light is allowed (79% at 550nm and 72.5% at 1200nm).

[0126] In the “bright-cool” mode, the transmittance of visible light remains almost unchanged, and the transmittance of near-infrared light is greatly reduced (70.5% at 550nm and 30.5% at 1200nm).

[0127] In the “dark cool” mode, the visible and near-infrared light transmittance drops further (26.5% at 550nm and 1.5% at 1200nm).

[0128] There are also changes in its own thermal radiation in the mid-infrared before and after color change. In the range of 8.5μm to 9.5μm, the emissivity modulation is 0.51, and in the range of 9.5μm to 13μm, the emissivity modulation is 0.33.

[0129] The microstructure morphology and electrochromic performance of Example 3 were characterized, and the results are as follows:

[0130] Figure 2 For the microstructure and morphology characterization of Example 3, where:

[0131] Figure 2 a is the XRD pattern of thin film W4 on ITO. After removing the characteristic peaks of the substrate ITO, cubic phase WO3 is shown. It shows that adding Ti element can change WO3 from the previous monoclinic phase to cubic phase, with better stability.

[0132] Figure 2 b is the XPS full spectrum of thin film W4. It can be seen that there are four elements W, C, Ti, and O in the thin film.

[0133] Figure 2 In c, the high-resolution W 4f XPS spectrum peaks at 35.8eV and 37.9eV for W 6+ 4f 7 / 2 and 4f 5 / 2 , and peaks at 34.6eV and 36.6eV for W 5+ 4f 7 / 2 and 4f 5 / 2 , indicating that the carbothermal reduction of organic matter in the thin film produces oxygen vacancies, confirming the existence of WO 3-x (0 < x < 0.5). The existence of oxygen vacancies is beneficial to the improvement of electrochromic performance.

[0134] Figure 2 d is the high-resolution XPS spectrum of Ti 2p of W4. Ti 2p has two independent peaks at 458.9eV and 464.7eV, which are Ti 2p 3 / 2 and Ti 2p 1 / 2 , corresponding to the peaks of TiO2.

[0135] Figure 2 e is the SEM image of W4. It can be seen that the surface of the thin film is relatively flat and is a porous structure.

[0136] Figure 2 From the cross-sectional view of f, it can be seen that the average thickness of the thin film is about 1.4μm.

[0137] Using an electrochemical workstation, in 1 mol / L PC / LiClO4 electrolyte, with ITO and film as working electrodes, Ag / AgCl as reference electrode, and platinum sheet as counter electrode, the film was faded and colored under applied voltages of +1.5 V and -1.5 V, and then its transmittance was tested using a UV-Vis-NIR spectrophotometer.

[0138] Figure 3 It can be seen from a that the film exhibits high optical modulation amplitude in the visible-near infrared region, which is 76.22% at 700nm in the visible light and 70.87% at 1200nm in the near infrared. Figure 3 As can be seen in a, under different voltages, the film exhibits dynamic modulation of visible-near-infrared light.

[0139] Figure 3 c is the change in the optical modulation amplitude of the film after 1000 CV cycles, which is 62.53% at 700nm and 58.29% at 1200nm, with a high retention rate and strong stability.

[0140] Figure 3 d is the functional diagram of the three optical modes of the film. Under forward bias, the transmittance of the film in the visible-near infrared region is very high, showing a "bright hot" mode; when a small negative voltage is applied, the transmittance of the film in the visible light region remains almost unchanged, while the near-infrared transmittance is greatly reduced, showing a "bright cold" mode; when a large negative voltage is applied, the visible-near infrared transmittance of the film is greatly reduced, showing a "dark cold" mode.

[0141] In order to study the performance of its own infrared thermal radiation, according to the Stefan-Boltzmann law E = εσT 4 (where E: radiation energy of the object, ε: surface emissivity of the object, σ: Stefan-Boltzmann constant, T: temperature of the object). The thermal radiation of the object itself can be adjusted by adjusting the surface emissivity of the object. We placed W4 on a heating table at 60°C in the colored (-1.5V) and faded (+1.5V) states, with the film side facing up. Figure 4 As shown in (a), after stabilization, the surface temperature was recorded with an infrared thermal imager. According to the law, the higher the temperature displayed on the infrared thermal imager, the greater the surface emissivity. The infrared emissivity of the two objects can be compared. Figure 4 By comparison in (b), it is found that the temperature in the faded state is lower, showing a low emissivity state, and the temperature in the colored state is higher, showing a high emissivity state. The final temperature difference between the two is 6.5°C, indicating that the mid-infrared emissivity can be regulated. Figure 4As can be seen in (c), in the mid-infrared 8.5μm~9.5μm, the emissivity is modulated by 0.5, and in the 9.5μm~13μm, the emissivity is modulated by about 0.3. Moreover, in the faded state, it presents a "bright hot" mode, while the low emissivity can ensure that the thermal radiation emitted outward is low, further enhancing the "bright hot" mode and achieving coordinated regulation of the three bands, while in the colored state, it collaboratively achieves the "dark cold" mode.

[0142] In summary, the present invention discloses a simple and economical method for preparing a multi-band electrochromic film, and studies the morphology, crystallinity and electrochromic performance of the obtained film. It realizes multi-band optical regulation and provides a feasible method for the preparation of multi-band electrochromic materials and devices.

[0143] At the same time, based on the films provided in Examples 1-8 of the present invention, any of the films can be used in the preparation of smart windows, smart car windows, electrochromic displays, smart thermal management materials or color-changeable camouflage military equipment.

[0144] The above-mentioned embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person skilled in the art, several modifications, improvements and substitutions can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached claims.

Claims

1. Multi-band electrochromic composite film, characterized in that: The film has, An optical modulation amplitude of 70% to 78% at a light wavelength of 700 nm; and / or, An optical modulation amplitude of 65% to 72% at a light wavelength of 1200 nm; and / or, In "bright heat" mode, the transmittance is 75% to 82% at a wavelength of 550nm and 70% to 75% at a wavelength of 1200nm; and / or, In the "bright cold" mode, the transmittance is 65% to 72% at a wavelength of 550nm, and the transmittance is 28% to 35% at a wavelength of 1200nm; and / or, In the "dark and cold" mode, the transmittance is 23% to 28% at a light wavelength of 550nm, and the transmittance is 0.8% to 2% at a light wavelength of 1200nm.

2. The multi-band electrochromic composite film according to claim 1, characterized in that: The film also has, In the 8.5 μm to 9.5 μm band, an emissivity modulation amplitude of 0.4 to 0.6; and / or, In the 9.5μm to 13μm band, the emissivity modulation amplitude is 0.2 to 0.

4.

3. The multi-band electrochromic composite film according to claim 2, characterized in that: The film has a thickness of 0.2 μm to 1.5 μm.

4. The multi-band electrochromic composite film according to any one of claims 1 to 3, characterized in that: In the X-ray photoelectron energy spectrum, the 4f electron orbit of the tungsten element of the film has characteristic peaks at binding energies of 35.8 eV, 37.9 eV, 34.6 eV and 36.6 eV.

5. The multi-band electrochromic composite film according to claim 4, characterized in that: In the X-ray photoelectron spectrum, the 2p electron orbit of the titanium element of the film has a characteristic peak at a binding energy of 458.9 eV or 464.7 eV.

6. The method for preparing the multi-band electrochromic composite film according to any one of claims 1 to 5, characterized in that: The following steps are included: S1. Add 5-10 mL H2O2 to every 1-3 g tungsten powder in an ice-water bath, stir slowly until the solution is transparent, add AcOH and EtOH in sequence, continue stirring until the solution is clear, and after aging, obtain WO 3-x Precursor colloid; the volume ratio of H2O2, AcOH, and EtOH is 5-10:1-3:5-10; S2. The WO 3-x Titanium source was added to the precursor colloid and ultrasonic hydrolyzed to obtain WO 3-x / TiO2 composite precursor colloid, use 126-378μL titanium source for every 1-3g tungsten powder; S3. The WO 3-x After adding a film-forming agent to the TiO2 composite precursor colloid, the film is spin-coated on a transparent conductive substrate, carbonized at 150°C to 250°C for 10min to 30min, gradually heated to 350°C to 450°C, and annealed to obtain the film.

7. The method for preparing the multi-band electrochromic composite film according to claim 6, characterized in that: The transparent conductive substrate is ITO glass or FTO glass.

8. The method for preparing the multi-band electrochromic composite film according to claim 6, characterized in that: The titanium source is one or more of tetramethyl titanate, tetraisopropyl titanate, tetra-n-butyl titanate or tetraethyl titanate.

9. The method for preparing the multi-band electrochromic composite film according to claim 6, characterized in that: The film-forming agent is PEG600; the added amount of the film-forming agent is 0.07 mL to 0.28 mL.

10. Application of multi-band electrochromic composite film, characterized by: Use of the film according to any one of claims 1 to 5 in the preparation of smart windows, smart car windows, electrochromic displays, smart thermal management materials or color-changeable camouflage military equipment.

Citation Information

Patent Citations

  • Tungsten trioxide-titanium dioxide electrochromic film and preparation method thereof

    CN113800781A

Cited By

  • Self-recovery photochromic material and preparation method thereof

    CN122609221A